A Southern Indian Ocean database of hydrographic profiles obtained with instrumented elephant seals - Roquet, Fabien; Williams, Guy; Hindell, Mark A.; Harcourt, Rob; McMahon, Clive; Guinet, Christophe; Charrassin, Jean-Benoit; Reverdin, Gilles; Boehme, Lars; Lovell, Philip; Fedak, Mike (Scientific Data, 2015)
The instrumentation of southern elephant seals with satellite-linked CTD tags has offered unique temporal and spatial coverage of the Southern Indian Ocean since 2004. This includes extensive data from the Antarctic continental slope and shelf regions during the winter months, which is outside the conventional areas of Argo autonomous floats and ship-based studies. This landmark dataset of around 75,000 temperature and salinity profiles from 20–140 °E, concentrated on the sector between the Kerguelen Islands and Prydz Bay, continues to grow through the coordinated efforts of French and Australian marine research teams. The seal data are quality controlled and calibrated using delayed-mode techniques involving comparisons with other existing profiles as well as cross-comparisons similar to established protocols within the Argo community, with a resulting accuracy of ±0.03 °C in temperature and ±0.05 in salinity or better. The data offer invaluable new insights into the water masses, oceanographic processes and provides a vital tool for oceanographers seeking to advance our understanding of this key component of the global ocean climate. Peer reviewed